Psychometric properties and cultural adaptation of the Polish Version of the Gay Affirmative Practice Scale - Piotr Karniej; Piotr Karniej; Anthony Dissen; Raúl Juárez-Vela; Iván Santolalla-Arnedo; Teresa Sufrate-Sorzano; Maria Elena Garrote-Camara; Michał Czapla; Michał Czapla; Michał Czapla (Frontiers Media S.A., 2024)
IntroductionThe lesbian, gay, bisexual, and transgender (LGBT) people often face unique medical disparities, including obstacles to accessing adequate and respectful care. The purpose of this study was to test the psychometric properties(internal consistency, reliability, and factor structure) of the Polish-language version of the Gay Affirmative Practice Scale (GAP-PL).MaterialThe study was conducted over a 6-month period in 2023, from February to June, involving 329 medical students and professionals who evaluated the GAP-PL.MethodsBefore testing the psychometric properties of the original Gay Affirmative Practice Scale (GAP), it was translated and adapted from the original English language version into the Polish language. Authors then tested the psychometric properties of the tool on a sample of 329 participants. The internal coherence of the questionnaire was tested with the analysis of verifying factors (Confirmatory Factor Analysis). Cronbach alpha and the discriminatory power index were used as internal consistency measures.ResultsThere were more female than male participants (55.32%). More than 53% of the participants were heterosexual, and the average age of the respondents was ~30 years. The internal consistency of the Polish-language version and its domains was strong with the overall Cronbach's alpha ranges for each subscale domains ranging between 0.936 and 0.949. The McDonald's omega coefficient was 0.963.ConclusionThe GAP-PL has excellent properties of factorial validity and can be used in research and clinical practice in Polish-speaking populations.